2012
DOI: 10.1016/j.jmaa.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Long-time behavior of a model of extensible beams with nonlinear boundary dissipations

Abstract: a b s t r a c tThis paper is concerned with the long-time behavior of a model of extensible beams continuous nonnegative function andh is a static load. To this problem little is known with nonlinear boundary conditions. One considers the case where a nonlinear forcing interacts with the shear force at the boundary. Then the existence of a global attractor is proved with a sole boundary damping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…In the case of nonlinear clamped and hinged beams, the well-posedness has been known for sometime; consult the abstract theory in [12] and note the classical references (for both 1-D Krieger and 2-D Berger nonlinearities) [2,3,5,15,21]. In the case of the cantilevered beam CF with α ≥ 0, see the recent work [26] (which includes discussion of other cantilevered beams [33]).…”
Section: Well-posednessmentioning
confidence: 99%
“…In the case of nonlinear clamped and hinged beams, the well-posedness has been known for sometime; consult the abstract theory in [12] and note the classical references (for both 1-D Krieger and 2-D Berger nonlinearities) [2,3,5,15,21]. In the case of the cantilevered beam CF with α ≥ 0, see the recent work [26] (which includes discussion of other cantilevered beams [33]).…”
Section: Well-posednessmentioning
confidence: 99%
“…In the case of the beam, we have demonstrated that simplification, which yields the beam model here in (1.5). Generally speaking, this model has been historically referred to in the literature as a Krieger or Krieger-Woinowsky beam [WK50,MNP12], for instance. In the case of the 2-D full von Kármán system, when one takes in-plane accelerations to be negligible, the so-called scalar von Kármán equation [Lag89,CL10] are obtained.…”
Section: Nonlinear Beam and Plate Modelsmentioning
confidence: 99%
“…In [Ma03] the author considers the static version of the problem in [Ma01], with the associated nonlinear free boundary condition; that paper includes a very brief numerical study with specific polynomial nonlinear structure. The subsequent work [MNP12] is our primary motivating reference here, and addresses the dynamic equations with a general Berger-like nonlinearity from the point of view of attractors, following from [Ma03,MN10]. The latter analysis utilizes Lyapunov methods to demonstrate the dissipativity of the dynamical system, as well as a version of Theorem 8.3 to demonstrate asymptotic compactness.…”
Section: Berger Model For Cantilevered Beamsmentioning
confidence: 99%
“…[9]- [11], [19], [20] and references therein), and several kinds of plate equations with memory (see e.g. [8], [14], [22], [24]- [27]. Therefore, we point out that our abstract results can be applied on a large variety of partial differential equations in which memory effects are considered.…”
Section: Introductionmentioning
confidence: 92%
“…Plate equations with or without memory effects have been attracted many researchers with various purposes. See [14]- [18], [22], [24], [26], [29], [31], [32] and references therein. Precisely, we present results concerning to the existence, uniqueness, regularity, unique continuation, blow-up alternative and continuous dependence of mild solutions to the strongly damped plate equation with memory (1.1)-(1.3).…”
Section: Introductionmentioning
confidence: 99%